Alopesia universalis pada anak yang berespon baik dengan terapi kombinasi: sebuah laporan kasus - I Gusti Ayu Agung Praharsini; I Gusti Ayu Agung Dwi Karmila; Ratih Purnamasari Nukana; Henny Wijaya (DiscoverSys Inc., 2022)
Background: Alopecia universalis is an autoimmune disease of the hair follicles, which results in complete loss of head and body hair. Until now there is no proven effective therapy in dealing with this disease. We report a case of alopecia universalis that responded well to combination therapy. Case: Female, 22 months old, complained by her parents due to hair loss on her head, eyebrows and eyelashes that had not grown back since the age of 8 months. On the fingernails and toenails found pitting nails, trachonycia. On scalp dermoscopy examination, multiple yellow dots were found. Severity of Alopecia Tool Score (SALT) was 100%. The patient was treated with minoxidil 5%, mometasone 0.1%, triamcinolone 12 mg and excimer laser. Administration of minoxidil increases prostaglandin production and maintains the anagen phase. Corticosteroids are immunosuppressive which suppress the immune attack of T cells on hair follicles. UV light on the excimer laser can reduce the proliferation of T lymphocytes, thereby reducing perifollicular inflammation and hair follicle damage. In this case, after 4 months of observation, the growth of terminal hair and vellus hair on the scalp, eyebrows and eyelashes was seen. On the patient's nails, the trachonycia was improved, with pitting nails remaining. SALT decreased to 58%. Conclusion: The combination therapy of minoxidil, corticosteroid and excimer laser gave good results in this case. During treatment, there were no side effects or recurrences. Latar belakang : Alopesia universalis adalah penyakit autoimun pada folikel rambut, yang mengakibatkan kerontokan seluruh rambut kepala dan tubuh. Hingga saat ini belum ada terapi yang terbukti efektif dalam menangani penyakit ini. Berikut dilaporkan kasus alopesia universalis yang memberikan respon baik dengan terapi kombinasi. Kasus: Pasien perempuan, 22 bulan, dikeluhkan orang tuanya mengalami rambut kepala, alis dan bulu mata yang rontok dan tidak tumbuh kembali sejak usia 8 bulan. Pada kuku tangan dan kaki didapatkan adanya pitting nails, trachonycia. Pada pemeriksaan dermoskopi kulit kepala didapatkan adanya multiple yellow dots. Severity of Alopecia Tool Score (SALT) 100%. Pasien diberikan terapi minoksidil 5%, mometason 0.1%, triamsinolone 12 mg dan laser excimer. Pemberian minoksidil meningkatkan produksi prostaglandin dan mempertahankan fase anagen. Kortikosteroid bersifat imunosupresif yang menekan serangan imunitas sel T pada folikel rambut. Sinar UV pada laser excimer dapat menurunkan proliferasi sel T limfosit sehingga mengurangi peradangan perifolikular dan kerusakan folikel rambut. Pada kasus, setelah pengamatan selama 4 bulan nampak adanya pertumbuhan rambut terminal dan rambut vellus pada kulit kepala, alis dan bulu mata. Pada kuku pasien nampak trachonycia membaik, tersisa pitting nails. SALT menurun menjadi 58%. Simpulan: Terapi kombinasi minoksidil, kortikosteroid dan laser excimer memberikan hasil yang baik pada kasus ini. Selama pengobatan tidak didapatkan adanya efek samping dan rekurensi.